Association between homicide and myocardial infarction mortality: a population-level analysis in Mexico from 2000 to 2019 - Omar González-Santiago (Faculty of Medicine, Universitas Trisakti, 2026)
BackgroundGlobally, violent deaths represent a serious public health issue, and Mexico has shown an increase in homicides. Exposure to violence has been linked to adverse mental and physical health outcomes, including cardiovascular disease. However, population-level evidence linking homicide mortality to myocardial infarction (MI) mortality remains limited. This study assesses the association between homicides and mortality from myocardial infarction in Mexico from 2000 to 2019. MethodsThis ecological time-series study used national mortality data from the Mexican National Institute of Statistics and Geography (INEGI). Adjusted annual mortality rates were calculated. Mortality trends were evaluated using Joinpoint software. The association between homicides and other causes of mortality was analyzed using Pearson correlation and univariate and multivariate regression analyses. ResultsDuring the study period, the average adjusted mortality rates were 16.8/100,000 for homicides and 67.4/100,000 for myocardial infarction. Both homicide and MI mortality rates increased significantly over time. In simple linear regression, homicides only showed significant associations with myocardial infarction (B=0.55, p<0.05). In multivariate regression analyses, homicide mortality remained significantly associated with MI mortality after adjustment for unemployment, gross domestic product per capita (GDP-PC), and diabetes mortality, although the association was attenuated when suicide mortality was included in the model. ConclusionAt the population level, from 2000 to 2019 both homicide and MI mortality rates increased significantly, while homicides were positively associated with myocardial infarction mortality in Mexico. Elevated homicide rates act as a population-level stressor that coincides with higher mortality from heart attacks.